Selective Hydrogenation of Naphthalene to Decalin Over Surface‐Engineered α‐MoC Based on Synergy between Pd Doping and Mo Vacancy Generation. (16th March 2022) - Ma, Yufei; Liu, Jianbin; Chen, Meng; Yang, Qun; Chen, Hedong; Guan, Guoqing; Qin, Yanlin; Wang, Tiejun
Abstract: Although the hydrogenation of aromatics is important for the processing of fossil fuels and biofuels, it typically requires costly (e.g., noble metal‐based) catalysts and exhibits unsatisfactory selectivity. Herein, flake‐like nanocrystalline molybdenum carbide (α‐MoC) is surface‐engineered via Pd doping, and the synergy between the in‐situ generated Mo vacancies and doped Pd species is shown to promote the selective hydrogenation of naphthalene to decalin. Experimental and theoretical evidence reveal that this enhanced performance is due to the optimization of naphthalene adsorption energy and the establishment of a unique surface structure due to (i) surface environment modulation, (ii) the adjustment of electron density around Mo atoms, and (iii) the change in the strength of Mo‐H bonding caused by d‐band center optimization. Benefiting from the unique surface structure, the obtained optimum 0.5% Pd‐α‐MoC catalyst exhibits excellent performance. The developed strategy is successfully used to fabricate other noble metal (Pt, Ru)‐doped α‐MoC catalysts, thus holding promise as a universal method for the rational design of high‐performance metal carbide‐based hydrogenation catalysts. Abstract : The synergy between the Pd doping of flake‐like molybdenum carbide (α‐MoC) and Mo vacancy generation on its surface is used to adjust the electron density and d‐band center position and thus establish a unique surface structure promoting the selective hydrogenation of naphthalene to decalin.